The General Ordinances of the City of Indianapolis. Containing also, Acts of the Indiana General Assembly so far as they Control Said City, to which Prefixed a Chronological Roster of Officers from, 1832 to 1904 and Rules Governing the Common Council Page 551 § 1665-1668 - (:unkn) unknown (General Publisher, 1884)
Prohibited operating a shooting gallery for rifles or pistols without obtaining a license. Licenses shall cost twenty-five dollars for six-months or fifty dollars for one year. Violators fined fifty dollars for each day in violation.
--
Keywords: SHOOTING RANGES OR GALLERIES